‘‘A journey back to my wholeness’’: A qualitative metasynthesis on the relational and sexual recovery process of child sexual abuse survivors - Guyon, Roxanne; Fernet, Mylène; Godbout, Natacha (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2020)
Objective: This study aims to document the relational and sexual recovery process of child sexual abuse (CSA) survivors. Method: Using the framework-based synthesis approach (Dixon-Woods, 2011), a metasynthesis was conducted on qualitative peer-reviewed studies published between 2004 and 2019, focusing on the recovery from relational and sexual outcomes related to CSA experiences. Criteria of inclusion: 1) included self-identified men or women who had sustained sexual abuse in childhood; 2) focused on CSA related relational or sexual outcomes and recovery processes; 3) included a qualitative component incorporating interviews or focus groups; 4) were carried out in Western countries. According to these criteria, a sample of eight articles was constituted. A direct content analysis was performed using The Drive to Move Forward Framework (Ochocka et al., 2005). Results: Findings yielded three main categories that illustrate the relational and sexual recovery process of CSA survivors: 1) The Drive to Move Forward after CSA; 2) Positive Strategies Mobilized to Recover from Relational and Sexual Issues Left by CSA and; 3) Social Circumstances that Facilitate or Hinder the Relational and Sexual Recovery Process. Conclusion: Although their relational and sexual recovery process may involve setbacks, and that they may be confronted with impeding social circumstances, survivors mobilize strategies and social resources to help them move forward after CSA. Implication: In order to help CSA survivors in achieving a satisfying relational and sexual life, providers should adopt a personalized approach that respects their process of relational and sexual recovery and adopt an ecological perspective to better understand the factors that can modulate this process.